The benefit and risk of addition of chemotherapy to EGFR tyrosine kinase inhibitors for EGFR-positive non-small cell lung cancer patients with brain metastases: a meta-analysis based on randomized controlled trials - Chen, Zhigang; Fu, Xiang; Zhu, Lingping; Wen, Xiurong (Frontiers in Oncology, 2024)
BackgroundCombining epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) with chemotherapy (ETC) offers more advantages for patients with EGFR-positive non-small cell lung cancer (NSCLC) than using EGFR TKIs alone (ET). However, whether this conclusion applies to patients with brain metastases (BM) remains controversial. This meta-analysis was performed to evaluate the benefits and risks of the two groups.MethodsSix databases were systematically searched for relevant literatures comparing ETC versus ET in treating EGFR-positive NSCLC patients with BM. The primary outcome assessed was overall survival (OS), while secondary outcomes included progression-free survival (PFS), and central nervous system (CNS)-PFS, responses, progression status and safety.ResultsSeven studies based on five randomized clinical trials with 550 patients were included. The ETC group exhibited better OS (hazard ratio [HR]: 0.64 [0.48, 0.87]), PFS (HR: 0.42 [0.34, 0.52]), and CNS-PFS (HR: 0.42 [0.31, 0.57]). The benefits in survival for OS, PFS, and CNS-PFS were validated in nearly all subgroups. Meanwhile, the overall objective response rate (ORR) (risk ratio [RR]: 1.25 [1.02, 1.52]) and CNS-ORR (RR: 1.19 [0.93, 1.51]) also tended to favor the ETC group. However, the addition of chemotherapy also brought about more grade 3-5/serious adverse events (AEs). The top five grade 3-5 AEs in the ETC group were alanine aminotransferase increase (11.25%), neutropenia (7.5%), nausea (7.5%), anorexia (5%), and diarrhea (5%).ConclusionsETC appears to be better than ET in treating EGFR-positive NSCLC patients with BM, with better OS, PFS, CNS-PFS, and responses. However, its poorer safety profile also needs to be taken into consideration.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024551073.